Upaya Peningkatan SDM Yayasan Pondok Sakinah melalui Pelatihan Soft Skill dan Hard Skill (Kedisiplinan, Akuntansi, dan Perpajakan) - Sri Agustini; Dewi Gunherani; Muliyani Muliyani; Widiyanti Rahayu Budi Astuti; Fithrah Kamaliyah (Jurnal Pengabdian Pada Masyarakat, 2021)
EFFORTS TO IMPROVE HUMAN RESOURCES OF PONDOK SAKINAH FOUNDATION THROUGH SOFT SKILL AND HARD SKILL TRAINING (DISCIPLINE, ACCOUNTING, AND TAXATION). The Pondok Sakinah Foundation aims to build a generation of people who are intellectually capable, morally elegant, and focus on learning the totality of piety, which is the hope of Indonesian Muslims. The Accounting Study Program (Prodi) of Pamulang University (Unpam) plays an active role in improving the quality of life of the community through Community Service (PKM). Community Service is education which is then continued with research which is actually a preparation to face real cases. Research is also a contribution from universities, especially lecturers, to the community. PKM is implemented by providing training on emotional intelligence, discipline, accounting and taxes. The program was chosen because it is considered important and is expected to provide education to the students. The material provided is an important material as their provision to increase their knowledge. By obtaining these materials, it is hoped that they can become people who are able to manage their own emotions and are disciplined in managing and applying the material provided.